Answer: The correct option is (c) 4n - 7.
Step-by-step explanation: We are given to find the general term for the following sequence :
-3, 1, 5, 9, . . . .
In the sequence, we notice the following patter :
1 - (-3) = 5 - 1 = 9 - 5 = . . . =4.
So, there is a common difference of 4 between the consecutive terms and so the given sequence is an arithmetic one.
We know that
the n-th term of an arithmetic sequence with first term a and common difference d is given by
![a_n=a+(n-1)d.](https://img.qammunity.org/2020/formulas/mathematics/middle-school/x65i7tsqnbp2i4n8pqc3auuccapnecxfj8.png)
In the given sequence,
a = -3 and d = 4.
Therefore, the n-th term of the sequence will be
![a_n=-3+(n-1)*4=-3+4n-4=4n-7.](https://img.qammunity.org/2020/formulas/mathematics/middle-school/f6wdsj15ck7lhxw6lqfrbuxuwd1ptt2owr.png)
Thus, the required general term of the sequence is (4n - 7).
Option (c) is CORRECT.